Protective Effect of Vitamins C and E against Gasoline Vapors Induced Haematological and Biochemical Changes in Male Rats (Journal of Scientific Research, 2015)
The present work was designed to investigate the changes in some hematological, biochemical parameters and lipid profile as well as possible protective role of vitamins C and E against gasoline vapors induced toxicity in male rats. The present results showed that gasoline 80 vapors significantly decreased (p?0.05) the concentration of total serum protein (TSP) and albumin concentrations and increased (p?0.05) in serum activities of serum aminotransferases (ALT and AST) and alkaline phosphatase (ALP) compared to the control group. Also, exposure to gasoline 80 vapors induced significant decrease (p?0.05) in hemoglobin concentration, red blood cell count (RBCs), packed cell volume (PCV) and high density lipoprotein cholesterol (HDL-C) compared to control group. On the other hand, exposure to gasoline 80 vapors resulted in significant increase (p?0.05) in the levels of total cholesterol (TC), triglycerides (TGs), LDL-cholesterol (LDL-C) and very low density lipoprotein cholesterol (VLDL-C) relative to untreated experimental animals. However, concomitant treatment with gasoline vapors and administration of vitamins C and E exhibited a protective role on the observed toxic effect of gasoline vapors in male rats. The results of the present study indicated that toxic effects of gasoline vapors could be reduced by dietary supplementation of vitamins C and E.